Profile Of HIV Positive Antenatal Women in Tertiary Care Hospital in Surat City - Chaudhari, Pratixa Z; Chauhan, Jigisha U; Congathi, Satyanarayan A (National Journal of Community Medicine, 2014)
Background: HIV infection is a global epidemic that now affect 35 million people worldwide. Its rate is increasing in female day to day as well as 95% of pediatrics HIV infection occur through parent to child transmission .despite prenatal ART treatment still morbidity and mortality is rate is still high so the present study was conducted to identify HIV in ANC women and her husband for providing apparent care of ANC women and decrease risk of transmission to fetus as well as uninfected partners. Methods: This cross sectional study was carried out in tertiary care hospital of surat city include 1000 ANC women and her husband coming at ANC clinic for routine check up .all the women and husband counsel and tested for HIV before taking prior consent, also taken detail history to asses sociodemgraphic profile, obstetric profile and associated co morbidity in ANC women. Results: Among study population 0f 1000 women 19 women were HIV positive. seroprevalence is more in age less than 25 years illiterate(78.9%)unskilled(100%) coming from urban area(78.9%). 83.5% regularly registered multigravida(78.9%)and vaginally delivered (68.9%) ANC women were HIV positive. None of the seropositive women were hbsag positive, out of 19 seropositive 7(36.84%) anemic and 12 (63.6%) non anemic. Conclusion: Seroprevalence is more in younger multiparous, illiterate, unskilled registered ANC women. So proper counseling and timely management of delivery is needed by health personnel.